Length of hospital stay of orthopaedic inpatients in a tertiary care teaching hospital in Nepal - Bidary, Suraj; Pandey, Suresh; Gupta, Hemant Kumar; Aryal, Roshani; Bhattarai, Kushal (Journal of Chitwan Medical College, 2021)
Background: Length of Hospital Stay (LOHS) can have important effects on the cost of treatment and patient outcomes. The aim of this study was to determine the length of hospital stay among orthopaedic inpatients and assess its association with different socio-demographic and clinical factors. Methods: A retrospective study was conducted at College of Medical Sciences and Teaching Hospital, Nepal, wherein, clinical records of patients admitted and treated as inpatients between January and December 2019 were retrieved. Demographic data, diagnosis, treatment details, LOHS, co-morbidities, treatment modality and mode of payment were documented and data was analyzed using SPSS software 16.0. Median was calculated for skewed continuous data and frequency analysis was done for categorical variables. P value <0.05 was considered statistically significant. Results: In a total of 1248 patients with mean age of 33.8±18.7 years, 72.4 % (n=904) were male. Most of them (34.9%, n=435) were students and majority (62.5%, n=780) were from outside Chitwan. The median LOHS was 5.0 (3.0–10.0) days. It was significantly greater in cases from outside Chitwan, those with trauma, infection, associated injury, and complications (p<0.05). Moreover, there was significant difference in LOHS among various age quintiles, occupations, fracture types, modes of payment and treatment modalities (p<0.05). However, LOHS did not differ significantly between patients with or without co-morbidity and gender (p>0.05). Conclusions: This study identified that the LOHS was significantly associated with various clinico demographic factors except gender and co-morbidity. More studies can be conducted to assess the relationships further.